Genetic variability estimated in banana diploids through microsatellite markers - Amorim, Edson Perito; Reis, Ronaldo Viana dos; Santos-Serejo, Janay Almeida dos; Amorim, Vanusia Batista de Oliveira; Silva, Sebastião de Oliveira e (Pesquisa Agropecuaria Brasileira, 2008)
The objective of this work was to estimate the genetic diversity between 38 banana diploids from the banana breeding program of Embrapa Mandioca e Fruticultura Tropical (Embrapa Cassava and Tropical Fruits), including improved hybrids, cultivated and wild species, using fi fteen SSR markers. Genetic similarities were utilized to cluster genotypes through UPGMA, based on Jaccard coeffi cient. The average number of alleles per primer was 7.53, with a total of 113 alleles identifi ed. The average similarity was 0.22, and ranged from 0.028 to 0.48, indicating the existence of genetic variability between genotypes. The clustering analysis based on microsatellite polymorphism could not completely separate improved hybrids, cultivated and wild species. Some diploids grouped according to their geographic origins, among which Musa ornata and IAC-1, and Tjau Lagada and Lidi, while in others no relation was established. There was a trend of clustering among related diploids as: SH3263 and 8694-20; 4279-01 and 9179-03; 1304-06 and 5854-03; 86B79-10 and 7341-03; 86B79-12 and 0337-02; and 9194-04 and 4154-08.